Managing by Design - Gruber, Marc; de Leon, Nick; George, Gerard; Thompson, Paul (Academy of Management Journal, 2015)
This editorial written by myself and Marc Gruber of EPFL. It explores the role of design thinking in the management of large organisations, and focuses on how design principles can be applied to the design of the workplace and the nature of work itself. As Head of Service Design at the RCA, my contribution is on how to apply design thinking methods for managers and the 6 key elements described in this approach In the last decade the importance of design and the value of design thinking as a tool for innovation has been recognized by both business and government. Design has become a strategic tool for business helping to translate technological innovation into user value, connecting with consumer needs and creating compelling product and service experiences that create new business value. In this paper we consider a further application of design thinking by considering how managers can apply it to the design of the workplace experience. Many enterprises, especially those in the knowledge economy, are defined by their human resources and their capacity to attract and retain talent. In this competitive environment the design of the employee experience and the services that support them and enable them to deliver value to the clients and colleagues, is a key differentiator. Applying design thinking to the design of work itself, the systems that support it, and the physical and virtual environments in which it takes place can help business and organizational leaders to attract and retain top talent, as well as to enhance productivity and operational effectiveness. In this paper we explore the key factors and principles by which leaders and managers can apply design thinking to transform the workplace experience and we propose 6 key elements for managers to enable that transformation and enhance social capital and business and organisational performance.